Epstein–Barr virus patterns in US Burkitt lymphoma tumors from the SEER residual tissue repository during 1979–2009. Issue 1 (23rd April 2013) - Mbulaiteye, Sam M.; Pullarkat, Sheeja T.; Nathwani, Bharat N.; Weiss, Lawrence M.; Nagesh Rao,; Emmanuel, Benjamin; Lynch, Charles F.; Hernandez, Brenda; Neppalli, Vishala; Hawes, Debra; Cockburn, Myles G.; Kim, Andre; et al.
<x xml:space="preserve">Abstract</x> Burkitt lymphoma (BL) occurs at all ages, but the patterns of Epstein–Barr virus (EBV) positivity in relation to human immunodeficiency virus (HIV), immunoprofiles and age have not been fully explored. BL tissues from residual tissue repositories, and two academic centers in the United States were examined by expert hematopathologists for morphology, immunohistochemistry, MYC rearrangement, EBV‐encoded RNA (EBER), and diagnosed according to the 2008 WHO lymphoma classification. Analysis was done using frequency tables, Chi‐squared statistics, and Student's t‐test. Of 117 cases examined, 91 were confirmed as BL. The age distribution was 26%, 15%, 19%, and 29% for 0–19, 20–34, 35–59, 60+ years, and missing in 11%. MYC rearrangement was found in 89% and EBER positivity in 29% of 82 cases with results. EBER positivity varied with age (from 13% in age group 0–19 to 55% in age group 20–34, and fell to 25% in age group 60+ years, p = 0.08); with race (56% in Blacks/Hispanics vs 21% in Whites/Asians/Pacific Islanders, p = 0.006); and by HIV status (64% in HIV positive vs 22% in HIV negative cases, p = 0.03). EBER positivity was demonstrated in about one‐third of tumors and it was strongly associated with race and HIV status, and marginally with age‐group.